Toughening master batch with capacity increasing function and preparation method thereof
Through the blending and grafting modification technology of SEBS and TPU, a toughened masterbatch with compatibilization function is prepared, which solves the problem that polycarbonate is prone to stress cracking at low temperatures and significantly improves its low-temperature toughness and tensile strength. .
Patent Information
- Application Number
- CN202411575421.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-21
AI Technical Summary
Polycarbonate (PC) is prone to stress cracking at low temperatures, and its low temperature impact strength is significantly reduced, limiting its application range.
SEBS is blended with TPU, and its toughening properties are enhanced through graft modification technology to prepare a toughening masterbatch with compatibilization function. The method includes washing SEBS into silicone oil, mixing it with modified monomers, grafting modification, mixing it with TPU, and performing melt blending and granulation with pure PC.
Significantly improves the low-temperature toughness and tensile strength of PC, reduces the risk of stress cracking, and significantly increases the low-temperature impact strength of PC when the dosage of compatibilizer is within 20%.
Smart Images

Figure BDA0005121672140000071 
Figure BDA0005121672140000081
Abstract
Description
Technical Field
[0001] The invention relates to a toughening masterbatch with a volume-increasing function and a preparation method thereof. Background Art
[0002] Polycarbonate (PC) is a type of polymer containing carbonate groups in the molecular chain, mainly bisphenol Ah type PC. PC has a high glass transition temperature (145-155℃), high viscosity flow temperature, high melt viscosity, and a rigid benzene ring structure that makes it deform less under external forces and has stable product dimensions. PC has excellent tensile strength and high impact strength at room temperature. However, in practical applications, PC still has some shortcomings. The rigid benzene ring structure limits the orientation of PC molecular chains. After being subjected to external forces, the orientation is not easy to relax, and the residual internal stress of the molecular chain is difficult to eliminate. The internal stress is frozen, making PC products prone to stress cracking. As the temperature decreases, the notch sensitivity of PC increases significantly, and the impact strength below 0℃ is much lower than that at room temperature, which limits the application range of PC. In some ultra-low temperature occasions (below -40℃), polyurethane or epoxy resin is often used, which undoubtedly increases the material cost.
[0003] In the low-temperature toughening modification of PC, polymers containing rubber soft segments are commonly used toughening agents, which can effectively improve the notch sensitivity of PC and improve the impact low-temperature strength. However, styrene and ACR elastomers have limited low-temperature toughening effects on PC.
[0004] Mixing SEBS with other polymers is the most versatile and economical method in industrial environments. Thermoplastic polyurethane (TPU) is an important engineering material with a microphase separation structure. Alternating diisocyanates and so-called "chain extender" molecules form (i.e., diols or diamines) glassy or semi-crystalline hard segments, while linear long-chain diols form rubbery soft segments. TPU is a multi-purpose polymer. They exhibit a wide range of physical properties, such as good mechanical properties, elastic properties, hardness and thermal stability. Blending SEBS with TPU can improve the tensile strength, thermal stability and polarity of SEBS. The present invention thus provides a toughening masterbatch with a compatibilizing function and a preparation method thereof. Summary of the invention
[0005] The present invention aims to solve the problems existing in the prior art and provides a method for preparing a toughening masterbatch with a volume-increasing function.
[0006] The technical solutions adopted in the present invention are:
[0007] A method for preparing a toughening masterbatch with a capacity-increasing function comprises the following steps:
[0008] 1) After flushing the SEBS with silicone oil, let it stand for later use, and dry the PC for later use;
[0009] 2) dissolving the initiator in the modified monomer, mixing it with the oil-washed SEBS after it is completely dissolved, and then kneading it to obtain the graft-modified SEBS;
[0010] 3) crushing the graft-modified SEBS and mixing it with TPU in an internal mixer;
[0011] 4) The blend obtained in step 3) is uniformly mixed with pure PC, and then dried in an oven, and melt-blended and granulated by a twin-screw extruder to obtain the masterbatch.
[0012] 2. The method for preparing a toughening masterbatch with a volume-increasing function as claimed in claim 1, characterized in that: in step 1), SEBS is flushed into silicone oil at an oil-increasing ratio of 20%-60% and then left to stand for use; the silicone oil is one of methyl vinyl silicone oil and methyl phenyl vinyl silicone oil, with a molecular weight of 20,000-60,000.
[0013] Furthermore, the modified monomer is one of glycidyl methacrylate, maleic anhydride, and allyl bisphenol A ether. In step 2), the amount of the modified monomer is 1%-2% of the mass of the graft-modified SEBS.
[0014] Furthermore, the initiator is one of persulfates, dicumyl peroxide, di-tert-butyl peroxide, and tert-butyl perbenzoate. In step 2), the amount of the initiator is 0.1%-0.5% of the mass of the graft-modified SEBS.
[0015] Furthermore, in step 2), the grafting reaction temperature is 180-200°C.
[0016] Furthermore, in step 3), the SEBS and TPU are mixed in a mass ratio of (20-40):(80-60).
[0017] Furthermore, the TPU is of polyester type, polyether type or butadiene type, and has a molecular weight of 400,000-800,000.
[0018] Furthermore, in step 4), the ratio of pure PC to the blend is selected as (70-90):(10-30).
[0019] The invention also discloses a toughening masterbatch prepared by the method.
[0020] The present invention has the following beneficial effects:
[0021] 1. The present invention uses TPU, SEBS and vinyl silicone oil as monomers to obtain a SEBS / TPU silicone oil ternary blend through free radical copolymerization, and grafts a GMA component. The copolymer prepared by the method of the present invention has a high content of elastomer components, multiple and long side chains, and can effectively improve the volume-increasing and toughening effects.
[0022] 2. The low-temperature toughening masterbatch SEBS / TPU silicone oil terpolymer prepared by the present invention has an extremely low glass transition temperature and excellent low-temperature resistance; the compatibilizer is further grafted and modified, and the GMA component and the grafted monomer are used to further enhance the compatibilization effect, and while increasing the volume, the synergistic toughening effect of the rubber component, the elastomer and the silicone oil is fully utilized, and the low-temperature toughness of PC can be significantly increased when the dosage is within 20%, and the decrease in tensile strength can be controlled within 10%. DETAILED DESCRIPTION
[0023] Example 1
[0024] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a 20% oil-to-oil ratio and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 20,000; PC is dried at 100°C for later use.
[0025] (2) GMA grafted SEBS: 0.5% DCP was dissolved in 2% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after it was completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0026] (3) Preparation of SEBS / TPU / silicone oil / PC composite materials:
[0027] The GMA grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer, the ratio of SEBS to TPU was 20:80, and the temperature of the internal mixer was 200°C.
[0028] Then, the SEBS / TPU / silicone oil blend was evenly mixed with pure PC, the ratio of pure PC to SEBS / TPU blend was selected to be 80:20, and then dried in an oven at 100° C. for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material, and finally the masterbatch was obtained.
[0029] Example 2
[0030] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a 20% oil-to-oil ratio and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 20,000; PC is dried at 100°C for later use.
[0031] (2) GMA grafted SEBS: 0.5% DCP was dissolved in 4% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after it was completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0032] (3) Preparation of SEBS / TPU / silicone oil / PC composite materials:
[0033] The GMA grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer, the ratio of SEBS to TPU was 30:70, and the temperature of the internal mixer was 200°C.
[0034] Then, the SEBS / TPU blend was evenly mixed with pure PC, the ratio of pure PC to SEBS / TPU / silicone oil blend was selected to be 80:20, and then dried in an oven at 100° C. for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material, and finally the masterbatch was obtained.
[0035] Example 3
[0036] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a 20% oil-to-oil ratio and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 20,000; PC is dried at 100°C for later use.
[0037] (2) GMA grafted SEBS: 0.5% DCP was dissolved in 6% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after it was completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0038] (3) Preparation of SEBS / TPU / silicone oil / PC composite materials:
[0039] The GMA grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer, the ratio of SEBS to TPU was 40:60, and the temperature of the internal mixer was 200°C.
[0040] Then, the SEBS / TPU blend was evenly mixed with pure PC, the ratio of pure PC to SEBS / TPU / silicone oil blend was selected to be 80:20, and then dried in an oven at 100° C. for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material, and finally the masterbatch was obtained.
[0041] Example 4
[0042] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a 40% oil-to-oil ratio and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 20,000; PC is dried at 100°C for later use.
[0043] (2) GMA grafted SEBS: 0.5% DCP was dissolved in 2% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after it was completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0044] (3) Preparation of SEBS / TPU / silicone oil / PC composite materials:
[0045] The GMA grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer, the ratio of SEBS to TPU was 20:80, and the temperature of the internal mixer was 200°C.
[0046] Then, the SEBS / TPU blend was evenly mixed with pure PC, the ratio of pure PC to SEBS / TPU / silicone oil blend was selected to be 80:20, and then dried in an oven at 100° C. for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material, and finally the masterbatch was obtained.
[0047] Example 5
[0048] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a 40% oil-to-oil ratio and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 20,000; PC is dried at 100°C for later use.
[0049] (2) GMA grafted SEBS:
[0050] 0.5% DCP was dissolved in 4% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after being completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0051] (3) Preparation of SEBS / TPU / silicone oil / PC composite materials:
[0052] The GMA grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer, the ratio of SEBS to TPU was 30:70, and the temperature of the internal mixer was 200°C.
[0053] Then, the SEBS / TPU blend was evenly mixed with pure PC, the ratio of pure PC to SEBS / TPU / silicone oil blend was selected to be 70:10, and then dried in an oven at 100° C. for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material, and finally the masterbatch was obtained.
[0054] Example 6
[0055] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a 40% oil-to-oil ratio and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 20,000; PC is dried at 100°C for later use.
[0056] (2) GMA grafted SEBS: 0.5% DCP was dissolved in 6% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after it was completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0057] (3) Preparation of SEBS / TPU / silicone oil / PC composite materials:
[0058] The GMA grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer, the ratio of SEBS to TPU was 40:60, and the temperature of the internal mixer was 200°C.
[0059] Then, the SEBS / TPU blend was evenly mixed with pure PC, the ratio of pure PC to SEBS / TPU / silicone oil blend was selected to be 90:30, and then dried in an oven at 100° C. for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material, and finally the masterbatch was obtained.
[0060] Example 7
[0061] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a ratio of 60% to oil and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 20,000; PC is dried at 100°C and set aside.
[0062] (2) GMA grafted SEBS: 0.5% DCP was dissolved in 2% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after it was completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0063] (3) Preparation of SEBS / TPU / silicone oil / PC composite materials:
[0064] The GMA grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer, the ratio of SEBS to TPU was 20:80, and the temperature of the internal mixer was 200°C.
[0065] Then, the SEBS / TPU blend was evenly mixed with pure PC, the ratio of pure PC to SEBS / TPU / silicone oil blend was selected to be 80:20, and then dried in an oven at 100° C. for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material, and finally the masterbatch was obtained.
[0066] Example 8
[0067] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a ratio of 60% to oil and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 20,000; PC is dried at 100°C and set aside.
[0068] (2) GMA grafted SEBS: 0.5% DCP was dissolved in 4% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after it was completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0069] (3) Preparation of SEBS / TPU / silicone oil / PC composite materials:
[0070] The GMA grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer, the ratio of SEBS to TPU was 30:70, and the temperature of the internal mixer was 200°C.
[0071] Then, the SEBS / TPU blend was evenly mixed with pure PC, and the ratio of PC to SEBS / TPU / silicone oil blend was selected to be 80:20. After that, it was dried in an oven at 100° C. for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material, and finally the masterbatch was obtained.
[0072] Example 9
[0073] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a ratio of 60% to oil and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 20,000; PC is dried at 100°C and set aside.
[0074] (2) GMA grafted SEBS: 0.5% DCP was dissolved in 6% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after it was completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0075] (3) Preparation of SEBS / TPU / silicone oil / PC composite materials:
[0076] The GMA-grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer. The ratio of SEBS to TPU was 40:60, and the temperature of the internal mixer was 200°C.
[0077] Then, the SEBS / TPU blend was evenly mixed with pure PC, the ratio of pure PC to SEBS / TPU / silicone oil blend was selected to be 80:20, and then dried in an oven at 100° C. for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material, and finally the masterbatch was obtained.
[0078] Comparative Example 1
[0079] Pure PC was injection molded into standard specimens for testing.
[0080] Comparative Example 2
[0081] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a ratio of 60% to oil and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 40,000; PC is dried at 100°C for later use.
[0082] (2) GMA grafted SEBS: 0.5% DCP was dissolved in 6% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after it was completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0083] (3) Preparation of SEBS / TPU / PC composite materials:
[0084] The GMA grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer, the ratio of SEBS to TPU was 40:60, and the temperature of the internal mixer was 200°C.
[0085] Then, the SEBS / TPU blend was evenly mixed with pure PC, and the ratio of pure PC to SEBS / TPU blend was selected to be 80:20. After that, it was dried in an oven at 100°C for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material.
[0086] Comparative Example 3
[0087] (1) Raw material pretreatment: SEBS is flushed with silicone oil at a ratio of 60% to oil and then left to stand for 24 hours; the silicone oil is methyl vinyl silicone oil with a molecular weight of 60,000; PC is dried at 100°C for later use.
[0088] (2) GMA grafted SEBS: 0.5% DCP was dissolved in 6% GMA (the total weight is the total weight of DCP+GMA+SEBS), and after it was completely dissolved, it was mixed with the oil-washed SEBS, and then mixed in a banbury mixer.
[0089] (3) Preparation of SEBS / TPU / PC composite materials:
[0090] The GMA grafted SEBS was crushed with a crusher, and then the crushed SEBS was mixed with TPU in an internal mixer, the ratio of SEBS to TPU was 40:60, and the temperature of the internal mixer was 200°C.
[0091] Then, the SEBS / TPU blend was evenly mixed with pure PC, and the ratio of pure PC to SEBS / TPU blend was selected to be 80:20. After that, it was dried in an oven at 100°C for 4 hours, and melt-blended and granulated by a twin-screw extruder to prepare a composite material.
[0092] The prepared low-temperature toughened modified particles were melt-blended with PC at a ratio of 20:80 and injection molded into standard specimens for testing.
[0093] Application performance testing
[0094] The low-temperature toughened modified particles prepared in Examples 1-9 and Comparative Examples 1-3 were melt-blended with PC at a ratio of 20%, injection molded into standard specimens, and tensile and impact properties were tested according to GB / T 1040-2006 and GB / T 1843-2008, wherein the PC brand was Japanese Teijin K-1300. The test results are shown in Table 1.
[0095] Table 1
[0096]
[0097]
[0098] From the above data, we can see that:
[0099] (1) When the oil ratio is 60%, the GMA addition amount is 2%, and the SEBS / TPU ratio is 20 / 80, the notched impact strength and elongation at break of PC are significantly improved, especially the notched impact strength at low temperature is greatly improved, indicating that the SEBS / TPU grafted GMA low-temperature toughening masterbatch prepared by the present invention can well improve the toughness of PC, among which the toughening effect of Example 7 is the most obvious.
[0100] (2) In the preparation of the toughening masterbatch of the present invention, the molecular weight of the silicone oil is between 20,000 and 60,000, and the low-temperature toughness of the PC resin is improved to a certain extent. When methyl vinyl silicone oil with a molecular weight of about 20,000 is selected, the low-temperature toughening effect of the prepared masterbatch is the best.
[0101] (3) During the preparation process, the use of low molecular weight silicone oil with a higher mass fraction can increase the silicone content in the copolymer, and the use of glycidyl methacrylate to graft the compatibilizer can effectively enhance the compatibilization effect of the copolymer and obtain better low-temperature toughening effect.
[0102] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principle of the present invention, and these improvements should also be regarded as within the protection scope of the present invention.
Claims
1. A method for preparing a toughening masterbatch with a capacity-increasing function, characterized in that: The steps include: 1) After flushing the SEBS with silicone oil, let it stand for later use, and dry the PC for later use; 2) Dissolve the initiator in the modified monomer, mix it with the oil-washed SEBS after it is completely dissolved, and then mix it to obtain the grafted modified SEBS; 3) Grind the grafted modified SEBS and mix it with TPU in an internal mixer; 4) The blend obtained in step 3) is uniformly mixed with pure PC, and then dried in an oven, and melt-blended and granulated by a twin-screw extruder to obtain the masterbatch.
2. The method for preparing a toughening masterbatch with a volume-increasing function according to claim 1, characterized in that: In step 1), SEBS is injected with silicone oil at an oil injection ratio of 20%-60% and then left to stand for use; the silicone oil is one of methyl vinyl silicone oil and methyl phenyl vinyl silicone oil, and has a molecular weight of 20,000-60,000.
3. The method for preparing a toughening masterbatch with a volume-increasing function according to claim 1, characterized in that: The modified monomer is one of glycidyl methacrylate, maleic anhydride, and allyl bisphenol A ether. In step 2), the amount of the modified monomer is 1%-2% of the mass of the graft-modified SEBS.
4. The method for preparing a toughening masterbatch with a volume-increasing function according to claim 1, characterized in that: The initiator is one of persulfates, diisopropylbenzene peroxide, di-tert-butyl peroxide, and tert-butyl perbenzoate. In step 2), the amount of the initiator is 0.1%-0.5% of the mass of the graft-modified SEBS.
5. The method for preparing a toughening masterbatch with a volume-increasing function according to claim 1, characterized in that: In step 2), the grafting reaction temperature is 180-200°C.
6. The method for preparing a toughening masterbatch with a volume-increasing function according to claim 1, characterized in that: In step 3), the SEBS and TPU are mixed in a mass ratio of (20-40):(80-60).
7. The method for preparing a toughening masterbatch with a volume-increasing function according to claim 1, characterized in that: The TPU is of polyester type, polyether type or butadiene type, and has a molecular weight of 400,000-800,000.
8. The method for preparing the polycarbonate low-temperature toughening masterbatch with compatibilization function according to claim 1, characterized in that: In step 4), the ratio of pure PC to the blend is selected as (70-90): (10-30).
9. A toughened masterbatch obtained by the preparation method according to any one of claims 1 to 7.